2022
DOI: 10.1186/s12905-022-02028-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between endometriosis and risk of endometrial cancer and breast cancer: a meta-analysis

Abstract: Purpose Endometriosis (EMS) is confirmed pathophysiologically to be an estrogen-dependent disease, similar to endometrial hyperplasia/cancer and breast cancer. Epidemiological and biological data on endometriosis might explain links between endometriosis and these cancers. We sought to identify the differences in the risk of endometrial cancer and breast cancer between women with and women without endometriosis. Methods We searched PubMed, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 66 publications
0
24
1
Order By: Relevance
“…Globally, the prevalence of endometriosis among reproductive age women and girls is 10%, 46 despite the fact that the specific contribution of CS to this magnitude is unknown. Moreover, several studies have found significant association of endometriosis and an increased likelihood of developing various cancers including ovarian cancer, endometrial, and breast cancer 47,48 . Other than direct health implications, CS are associated with increased health expenditures 49,50 .…”
Section: Public Health Implications Of Cesarean Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, the prevalence of endometriosis among reproductive age women and girls is 10%, 46 despite the fact that the specific contribution of CS to this magnitude is unknown. Moreover, several studies have found significant association of endometriosis and an increased likelihood of developing various cancers including ovarian cancer, endometrial, and breast cancer 47,48 . Other than direct health implications, CS are associated with increased health expenditures 49,50 .…”
Section: Public Health Implications Of Cesarean Sectionmentioning
confidence: 99%
“…Moreover, several studies have found significant association of endometriosis and an increased likelihood of developing various cancers including ovarian cancer, endometrial, and breast cancer. 47,48 Other than direct health implications, CS are associated with increased health expenditures. 49,50 With the growing burden of health system financing, increased CS rate is likely to exert extra pressure to the health system that may be detrimental in LMICs.…”
Section: Public Health Implications Of Cesarean Sectionmentioning
confidence: 99%
“…Interestingly, endometriosis was associated with a minimally increased risk of breast cancer (less than 10%). Only rare studies reported an increased risk for estrogen receptor-positive (ERþ)/progesterone receptor-negative (PR) breast cancer (ERþ/PR: HR = 1.90, 95% CI = 1.44–2.50) [ 50 , 51 ].…”
Section: Endometriosis and Cancermentioning
confidence: 99%
“…The association with endometrial cancer is controversial [ 50 , 51 ] probably because some biases complicate analyses. For instance, patients with lean size (low BMI) have an increased risk of endometriosis [ 15 ].…”
Section: Endometriosis and Cancermentioning
confidence: 99%
“…KIR expression is also heterogenous due to allelic variation in KIR genes [70]. Of note, KIRs can exhibit both an inhibitory and activating type, and a decrease in the KIR2DS2 (an activating KIR that recognizes HLA-C1 allotypes and HLA-A*11:01) is associated with an increased risk of endometriosis, which is well-correlated with EC risk (Table 1) [73][74][75][76][77]. Integrins, such as α5(CD49e) and β1(CD29) (fibronectin receptor), are receptors of extracellular matrix proteins that typically exhibit low levels of expression on NK cells in adults but increase in some tumors [33,78] (Table 1).…”
Section: Introductionmentioning
confidence: 99%